2001
DOI: 10.3727/000000001783986819
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pancreatic Polypeptide as a Market of Transplanted Insulin-Producing Fetal Pig Cells

Abstract: Transplantation of insulin-producing fetal pancreatic tissue into diabetic recipients has been shown to normalize blood glucose levels after several months. This time period is required for the growth and maturation of the fetal tissue so insulin levels cannot be used as a marker of graft function while the beta-cell is immature. Therefore, we have examined the use of another pancreatic endocrine hormone, pancreatic polypeptide (PP), to monitor graft function. The cell that produces this hormone has been shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Levels of PI were highest 4 d after fetal pig pancreatic tissue was transplanted into the mice, but were still measurable for at least the next 17 d (Fig. Our current results are similar to those reported previously when serum levels of PP were used as a marker of graft viability for up to 3 wk after transplantation, but was absent thereafter (11). No attempt was made to measure levels of PI earlier than 4 d, but based on previous experiments it would be expected that PI would be measurable earlier than this (11).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Levels of PI were highest 4 d after fetal pig pancreatic tissue was transplanted into the mice, but were still measurable for at least the next 17 d (Fig. Our current results are similar to those reported previously when serum levels of PP were used as a marker of graft viability for up to 3 wk after transplantation, but was absent thereafter (11). No attempt was made to measure levels of PI earlier than 4 d, but based on previous experiments it would be expected that PI would be measurable earlier than this (11).…”
Section: Discussionsupporting
confidence: 90%
“…Previously we have shown that PP secretion could probably be used as a marker of viability at this time (11). Previously we have shown that PP secretion could probably be used as a marker of viability at this time (11).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This hormone was undetectable at all time points both before and after onset of PFO on day 7; suggesting that immaturity of the tissue [22], rather than blockage of nutrient supply was the reason. The controls, sera from mice transplanted with empty microcapsules, similarly had non-detectable levels of porcine C-peptide.…”
Section: Resultsmentioning
confidence: 89%